Método montessori en el proceso de enseñanza aprendizaje de los niños del subnivel II de educación inicial en la Unidad Educativa Pedro Pablo Egüez Baquerizo - Moreno Peralta, Lissette Paola (2023)
This research originates from considering the Montessori Method as an appropriate methodology in the teaching-learning process, which requires the creation of various environments prepared in order for children to access knowledge freely and at the same time. They promote their independence, with the adult or teacher being an observer and guide during their development. The main objective is to evaluate the Montessori method in the teaching-learning process of children from Sublevel II of Initial Education of the “Pedro Pablo Egüez Baquerizo” Educational Unit, since there are difficulties in the academic development of the students. This research is descriptive, part of a non-experimental design, has a quantitative approach, uses the inductive method and applies the survey technique, which has been carried out with the purpose of obtaining statistical results. The Montessori methodology contributes in a relevant way to the educational development of the student, since in each of its areas there are specific materials that are focused on the fulfillment of a specific objective in the child's being. To conclude, the significance of the Montessori method in relation to the teaching and learning of children is demonstrated, being one of the strategies of vital importance to contribute to the comprehensive, academic and social development of children.